Kecenderungan Penyelesaian Tindak Pidana Perzinahan Melalui Mekanisme Hukum Adat Manggarai di Desa Golo Wua Kecamatan Wae Ri’i Kabupaten Manggarai - Cici Paramita Indah Ayu Tamara Bili; Karolus Kopong Medan; Daud Dima Tallo (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The purpose of this research is to analyze the tendency of adultery crime settlement through Manggarai customary law mechanism in Golo Wua Village, Wae Ri'i Sub-District, Manggarai Regency. The research used in this thesis uses empirical juridical research methods or field research. The result of this research is that the community still upholds cultural values that bind the community to one another in the frame of family harmonization. The community also maintains the integrity of the family so that it uses customary law as a persuasive approach to maintain social relations. The community in Golo Wua Village has a limited economy and if they follow the formal legal process it can be a huge financial burden. The people of Golo Wua Village still hold tightly to the beliefs of their ancestors and most cases of adultery that occur there are also those who still have a close blood relationship between the two perpetrators so it is illegal if resolved by formal or national law and must be resolved using customary law. Suggestions are expected to the customary leader (Tua Golo) before imposing sanctions / fines on the perpetrators of adultery should be in accordance with the actions committed and can provide a deterrent effect in applying customary sanctions of traditional leaders and reaffirming the customary rules that have been agreed upon, then provide customary sanctions that minimize adultery cases.